The Role of the Principal as a Manager in Improving School Quality in Elementary Schools - Mukhayati, Siti; Senowarsito, Senowarsito; Maryanto, Maryanto (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study examines the role of the principal as a manager in improving school quality at SD Negeri 01 Pagergunung, Pemalang Regency. Using a qualitative descriptive approach with a case study design, this research explores the implementation of POAC managerial functions consisting of planning, organizing, actuating, and controlling in school management practices. Data were collected through in-depth interviews, observations, and documentation involving the principal, teachers, and school committee members, and were analyzed using an interactive analysis model. The findings indicate that the principal applies participatory and data-based planning grounded in the Education Report Card, organizes human resources according to teacher competencies, actively carries out academic supervision and professional development activities, and implements reflective and accountable controlling processes involving school stakeholders. These managerial practices foster a collaborative and professional school climate, strengthen teacher professionalism, enhance instructional quality, and support improvements in student learning outcomes. This study concludes that the effective application of POAC-based managerial leadership is a key factor in achieving sustainable school quality improvement in primary education.